Understanding The Relationship Between Communication Style, Good Corporate Governance, Corporate Social Responsibility, Tax Compliance, Ethical Leadership, And Public Trust - Nurjannah Nurjannah; Siti Rumenta; Muhammad Arif Rahman (Jurnal Publikasi Ilmu Manajemen, 2022)
This research aims to investigate the interplay between communication style, good corporate governance (CG), corporate social responsibility (CSR), tax compliance, ethical leadership, and public trust. Employing an exploratory approach, the study utilizes a conceptual framework that integrates these factors to understand their relationships within organizational contexts. Sampling will involve selecting key stakeholders from various industries renowned for their commitment to ethical practices. Data analysis will employ thematic analysis techniques to identify patterns and themes. The study anticipates uncovering insights into how effective communication, aligned with robust CG and ethical leadership, impacts CSR initiatives, tax compliance, and ultimately influences public trust in organizations.